APPLICATION SCHEDULE REMINDER PRAYER USING MACROMEDIA FLASH MX - Teuku Muda Perkasa Alam,; Cut Asiana Gemawaty, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Development of a rapid computerized cause the computer is not a new item for themiddle to upper levels of society. Today computers have become much-needed itemsto complete their jobs or accomplish all their tasks.As human beings we would never escape from errors or deficiencies, that we oftenneglect our obligations to the Almighty to fulfill all of His commands, such as prayeror praying five times fardhu the ruling must be implemented. Therefore, prayerreminder for this application is expected to be beneficial for the people who alwaysuse computers in completing their tasks, in order to always be reminded to carry outthe obligation to always pray on time.